Tuberculose: uma análise epidemiológica associada à prevalência no Estado do Pará entre 2017 e 2021 - MELO, Adria Lorena de Aquino (2023)
The objective of this study is to analyze the epidemiological factors associated with the prevalence of tuberculosis in the State of Pará, from 2017 to 2021. This is a retrospective and documentary cross-sectional ecological study carried out based on the records of tuberculosis cases reported in the System Information on Diseases of Notifications, available for consultation in the database of the Department of Informatics of the Unified Health System (DATASUS). A total of 24,193 cases were included in this study and the analyzes of the variables were divided into three categories: Epidemiological indicators; sociodemographic profile and clinical profile of the disease. According to the indicators, the following data were observed: the highest incidence of Tuberculosis (TB) was evaluated in 2019 with 5,507 (23%) cases; with a coefficient of approximately 64 cases/100,000 inhabitants and mortality of 1.48 TB deaths per 100,000 inhabitants. The analysis of the sociodemographic profile pointed to metropolitan region 1 as having the highest prevalence with 11,948 cases (50%); the male sex was predominant with a total of 16,252 (67%) cases; the age group from 25 to 34 years with 1,006 (24%) cases; the brown race with 18,206 (75%) cases; also shows 2,857 (12%) cases that correspond to the population deprived of liberty and only 328 (1%) cases were affected by the disease in a homeless population. Regarding the clinical profile: the pulmonary form remains with high rates compared to the others, with 21,441 (89%) cases; in 1st Bacilloscopy it is possible to infer that the highest rate in records points to positivity, with 14,614 (60%) cases; with regard to sputum culture, the factor not performed shows 20,790 (86%) cases; when it comes to the study of co-infection between TB and HIV, it is noted that 63% of the cases, ie 15,191, presented the notification as “negative”. However, there is a significant notification of the “Not performed” field, with 5,749 (24%) cases. Finally, most cases progressed to cure, with a total of 13,707 (57%). In view of this, the presentation of the analysis of these factors achieves the objective of the research and demonstrates an inclination to cover the alternative hypothesis stipulated, as this study should not take as valid the feeling that there is efficiency in the control of these cases.